2006
DOI: 10.1007/s00198-005-0002-0
|View full text |Cite
|
Sign up to set email alerts
|

A risk profile for identifying community-dwelling elderly with a high risk of recurrent falling: results of a 3-year prospective study

Abstract: Introduction: The aim of the prospective study reported here was to develop a risk profile that can be used to identify community-dwelling elderly at a high risk of recurrent falling. Materials and methods: The study was designed as a 3-year prospective cohort study. A total of 1365 community-dwelling persons, aged 65 years and older, of the population-based Longitudinal Aging Study Amsterdam participated in the study. During an interview in 1995/1996, physical, cognitive, emotional and social aspects of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
219
3
15

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 312 publications
(270 citation statements)
references
References 29 publications
(49 reference statements)
18
219
3
15
Order By: Relevance
“…A number of studies have also found a higher prevalence of falls among women 1,2,8,9,13 . However, the Longitudinal Ageing Study Amsterdam (LASA) found a similar frequency between men and women (24.4% and 24.9%, respectively) 12 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…A number of studies have also found a higher prevalence of falls among women 1,2,8,9,13 . However, the Longitudinal Ageing Study Amsterdam (LASA) found a similar frequency between men and women (24.4% and 24.9%, respectively) 12 .…”
Section: Discussionmentioning
confidence: 98%
“…In general, the main risk factors associated with recurrent falls are female gender, advanced age, low weight, previous falls and fractures, current use of psychotropic medication, muscle weakness, reduced gait speed, functional disability, sedentary lifestyle, fear of falling, cognitive deterioration, presence of hazards in the home, alcoholic beverage intake and diverse illnesses, such as diabetes mellitus, arthritis, depression, urinary incontinence, Parkinson's disease, dizziness and stroke 12 . Table 2 Clinical risk factors for recurrent falls in the Brazilian population according to recurrent falls in the previous year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations